2022
DOI: 10.1007/s10554-022-02779-6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial cardiopathy in young adults with embolic stroke of undetermined source: a myocardial deformation imaging analysis

Abstract: Background Atrial cardiopathy (AC) has emerged as a potential pathological thrombogenic atrial substract of embolic stroke of undetermined source (ESUS), even in the absence of atrial fibrillation. Left atrium (LA) myocardial deformation analysis may be of value as a subclinical marker of AC and a predictor of ESUS. Aims To compare LA mechanical function between ESUS cases and age and sex-matched controls. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…We initially identified 6897 articles, with 4292 excluded as duplicates and 2402 excluded as nonrelevant based on title and abstract screening. Full text was examined in 200 articles, with 29 fulfilling inclusion criteria for data analysis 6,7,14–40 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We initially identified 6897 articles, with 4292 excluded as duplicates and 2402 excluded as nonrelevant based on title and abstract screening. Full text was examined in 200 articles, with 29 fulfilling inclusion criteria for data analysis 6,7,14–40 …”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined meta‐regression bubble plots and performed an exclusion analysis to identify outlier studies for sources of influence. A number of studies were identified over all meta‐analysis studies, with resolution of heterogeneity observed following their exclusion 6,16,21–23,26,28,30,32,34,35,37,39 . Notably, the majority of outlier studies were observed in studies comparing CS‐ESUS to HC, indicating probable unidentified clinical covariates in patients compared with healthy participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations